Analisis Pengaruh Return on Asset Ratio, Debt to Asset Ratio dan Current Ratio dalam Model Zmijewski X-Score terhadap Prediksi Financial Distress pada Perusahaan Sub-sektor Restoran, Hotel, dan Pariwisata di Bursa Efek Indonesia - Usmany, Paul; Loupatty, Linda (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
This research aims to test and analyze the influence of Return on Assets, Debt to Asset Ratio, and Current Ratio on Financial distress in restaurant, hotel and tourism sub-sector companies listed on the Indonesia Stock Exchange in 2020-2022 using the Zmijewski X-Score model. The population in this study are all companies in the restaurant, hotel and tourism sub-sectors listed on the Indonesia Stock Exchange in 2020-2022. The sample used was 35 companies obtained using a saturated sampling technique (Census Technique). This research data uses secondary data, namely annual reports of companies in the restaurant, hotel and tourism sub-sectors listed on the Indonesia Stock Exchange for 2020-2022. The data analysis method uses Logistic Regression. Using the Zmijewski In 2021, around 94.29% of companies have the potential to go bankrupt and 5.71% do not have the potential to go bankrupt. In 2022, the potential for bankruptcy will be 88.57% and 11.43% of companies have no potential for bankruptcy. The research results show that Return On Assets, Debt to Asset Ratio, and Current Ratio do not have a significant effect on Financial Distress.